2016
DOI: 10.1097/ta.0000000000001106
|View full text |Cite
|
Sign up to set email alerts
|

Emergent non–image-guided resuscitative endovascular balloon occlusion of the aorta (REBOA) catheter placement

Abstract: When using the use of the mid-sternum landmark for REBOA balloon placement, the likelihood of balloon deployment in the LZ was 100% with an acceptable margin of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…A similar approach was proposed in the previous cadaver study [7]. However, we believe that our study is more suited for application with general trauma victims, in urban areas, comparing with the cadaver study.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A similar approach was proposed in the previous cadaver study [7]. However, we believe that our study is more suited for application with general trauma victims, in urban areas, comparing with the cadaver study.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, a simple and patient-based method is still needed to guide REBOA implementation in zone 1 and facilitate tis safe use in the emergency department or pre-hospital settings. A cadaver study [7] has indicated that mid-sternum (the mid point between the xiphoid process and sternal notch) may be useful for implementing REBOA. However, these findings may not extrapolate well to trauma patients because cadavers are typically representative of older patients and may also exhibit precise morphological differences from living humans [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, placement of the REBOA is easier in Zone 1 because it does not require to spot the inferior mesenteric artery and the iliac bifurcation under US, as it would be the case in Zone 3. In order to position correctly the REBOA, it is recommended to take half of the length of the sternum as a reference 16. For interventions in rural areas, when the evacuation time to a trauma centre is longer, the interest of specifically positioning the REBOA in Zone 3 if the bleeding is exclusively pelvic or junctional is justified because the duration of acceptable complete occlusion is 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular balloon placement is performed by fluoroscopic guidance or post-placement x-ray confirmation after blind insertion [15]. Recently it has been proposed an ultrasound guided wire advancement [16]. This is an important finding because the need for fluoroscopy is a major limitation to the use of REBOA in settings with limited medical infrastructure.…”
Section: Introductionmentioning
confidence: 99%